2020
DOI: 10.1002/jms.4501
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of volatile metabolites formed by molds on barley by mass and ion mobility spectrometry

Abstract: The contamination of barley by molds on the field or in storage leads to the spoilage of grain and the production of mycotoxins, which causes major economic losses in malting facilities and breweries. Therefore, on-site detection of hidden fungus contaminations in grain storages based on the detection of volatile marker compounds is of high interest. In this work, the volatile metabolites of 10 different fungus species are identified by gas chromatography (GC) combined with two complementary mass spectrometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…APCI, HESI, PTR, SIFT, and other related techniques can be expected to have similar inherent VOC selectivities [9]. Previous studies utilizing such techniques have identified several VOCs from Fusarium isolates based upon comparison to public databases and published reports of microbial VOCs [12]. The distinctive ions observed here do not appear to overlap with previously published Fusarium VOCs.…”
Section: Dart-ms As a Real Time Methods For Voc Detectionmentioning
confidence: 52%
See 2 more Smart Citations
“…APCI, HESI, PTR, SIFT, and other related techniques can be expected to have similar inherent VOC selectivities [9]. Previous studies utilizing such techniques have identified several VOCs from Fusarium isolates based upon comparison to public databases and published reports of microbial VOCs [12]. The distinctive ions observed here do not appear to overlap with previously published Fusarium VOCs.…”
Section: Dart-ms As a Real Time Methods For Voc Detectionmentioning
confidence: 52%
“…In contrast to techniques dependent upon gas-phase proton-transfer reactions, GC-EI-MS based approaches will have different selectivities. Other researchers have explored the complementary potential in using both EI and proton transfer-based techniques [12].…”
Section: Dart-ms As a Real Time Methods For Voc Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coating materials include divinylbenzene (DVB), polydimethylsiloxane (PDMS), carboxen (CAR), polyacrylate (PA) and carbon wide range (CWR). These coatings have been used solely or in combination (Table 1) [113,130,163]. Hence, SPME-based sampling consists of the preconcentration of the VOCs on a fiber via absorption, and the later thermal desorption (delivered) of the captured volatiles to the GC column or directly to the mass spectrometer instrument (see Figure 2) [114,128].…”
Section: Identification Of Vocs Of Fungal Originmentioning
confidence: 99%
“…Other chromatographic techniques use two consecutive separation columns (2-dimensional liquid chromatography) or columns of different sorbent chemistry, such as ionic exchangers (see Table 1) [14,113,129,134,143]. The most common ionization techniques used in combination with 2D liquid chromatography are the ambient pressure ionization techniques, such as electrospray ionization (ESI) [134,135,137,138,[140][141][142][143][144][145]150] and atmospheric pressure chemical ionization (APCI) [139,146].…”
Section: Identification Of Non-volatile Compounds Of Fungal Originmentioning
confidence: 99%